2015
DOI: 10.1093/ije/dyv096.211
|View full text |Cite
|
Sign up to set email alerts
|

Education Modifies the Association of Wealth with Obesity in Women in Middle-Income but not Low-Income Countries: an Interaction Study using Seven National Datasets, 2005–10.

Abstract: Background: Education and wealth may have different associations with female obesity but this has not been investigated in detail outside high-income countries. This study examines the separate and inter-related associations of education and household wealth in relation to obesity in women in a representative sample of low-and middle-income countries (LMICs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…43 Furthermore, one study has reported complex intermediate patterns with an interaction between wealth and education in relation to obesity among women in LMICs, which may explain the differences in patterns by education and wealth observed in our study. 44 Studies also found that lower SES groups had less screening and knowledge of cardiovascular risk factors, whereas those with the knowledge were more likely to make healthy behavioural changes, 45 and educational attainment and health literacy can modify the NCDs and risk factors in LMICs. 46 47 Our findings indicated that SES gradients in NCD prevalence qualitatively differed within and between countries by type of prevalence measurement, specific NCDs and SES indicators, and thus NCDs as a category cannot be considered as diseases of affluence or of poverty.…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, one study has reported complex intermediate patterns with an interaction between wealth and education in relation to obesity among women in LMICs, which may explain the differences in patterns by education and wealth observed in our study. 44 Studies also found that lower SES groups had less screening and knowledge of cardiovascular risk factors, whereas those with the knowledge were more likely to make healthy behavioural changes, 45 and educational attainment and health literacy can modify the NCDs and risk factors in LMICs. 46 47 Our findings indicated that SES gradients in NCD prevalence qualitatively differed within and between countries by type of prevalence measurement, specific NCDs and SES indicators, and thus NCDs as a category cannot be considered as diseases of affluence or of poverty.…”
Section: Discussionmentioning
confidence: 99%